Development of a view perception quantifying method for a holistic window performance assessment using a virtual environment - Abd-Alhamid, Fedaa Tawfiq (2020)
Working Environments designs shape occupants’ health and well-being. One of these design parameters is window design and its impact on view perception. The view is the transmitting visual information carried by daylight into the buildings providing a connection to the outdoor environment. There are significant gaps in our understanding of the window-occupant relationship that characterises the view quality perception, partially due to the difficulties combined with methodologies used in daylight studies and the absence of studies with a holistic approach to understand such relationship. In response, this thesis developed an inclusive methodology that could be used to evaluate view perception in three stages. The first stage incorporated the development and validation of an alternative visual representing environment that reflects the luminous characteristics of a real one using physically-based virtual reality technique. The collection of photometric properties and visual responses in real and virtual settings and the analysis of the collected data established the validity of the proposed methodology as an alternative representation method to study visual perceptions. The second stage included the development of a comprehensive assessment method to quantify view perception based on two case studies. The first study investigated variations in view perception resulted from different observing locations using subjective and objective (physiological) evaluations. The same assessment method was applied to the second study to assess the variation in view perception from different window sizes. The results of the second study were assessed in the third stage against optimised window sizes for energy and daylighting performance to provide a holistic window performance; as view perception, energy, and daylighting window performance are usually studied separately in the literature. Further reliability and correlation analyses were conducted on the data collected from the two studies on view perception to provide a refined methodology for future evaluations of view perception.